Incivility in higher education: A qualitative study - Mansoureh Sepehrinia; Mahboubeh Shali; Atefeh Vaezi (Preventive Care in Nursing and Midwifery Journal)
Background: Incivility is an indicator of the shortfalls of nursing education. As a universal goal, academic education promotes civility and respect among scholars, working professionals, and citizens. Objectives: This study aimed to explore the student’s perception of higher education incivility and the solutions for reducing or managing it. Methods: This descriptive qualitative study was conducted in the nursing school of five Iranian medical universities from December 2022 to June 2023. Focus group was used to collect data. A total of 10 group discussions were conducted with 22 PhD nursing students (two discussions in each university). Data were analyzed in MAXQDA V.18 software using conventional content analysis approach. Results: After encoding and classifying the data, three main categories were identified: "making a civil environment", "incivility cycle breaking", and "building an academic civil culture". Conclusion: Ethical behaviors included a need for awareness, education, and identification of incivility and organizational standards, policies, and a commitment from all levels of administration to address incivility behaviors. It is important to provide students with opportunities to reflect on their own and others’ behaviors to be more aware and adhere to professional values as part of human growth.